Person-centered maternity care and postnatal health: associations with maternal and newborn health outcomesAJOG MFM at a Glance - May Sudhinaraset, PhD; Amanda Landrian, MPH, PhD; Ginger M. Golub, MPH; Sun Y. Cotter, MPH; Patience A. Afulani, MBChB, MPH, PhD (Elsevier, 2021)
BACKGROUND: Limited evidence exists on how women's experiences of care, specifically person-centered maternity care during childbirth, influence maternal and newborn health outcomes. OBJECTIVE: This study aimed to examine the associations between person-centered maternity care and maternal and newborn health outcomes. STUDY DESIGN: Longitudinal data were collected with 1014 women who completed baseline at a health facility and followed up at 2 weeks and 10 weeks after birth. A validated 30-item person-centered maternity care scale was administered to postpartum women within 48 hours after childbirth. The person-centered maternity care scale has 3 subscales: dignity and respect, communication and autonomy, and supportive care. Bivariate and multivariable log Poisson regressions were used to examine the relationship between person-centered maternity care and reported maternal complications, newborn complications, postpartum depression, postpartum family planning uptake, exclusive breastfeeding, and newborn immunizations. RESULTS: Controlling for demographic characteristics, women with high total person-centered maternity care score at baseline had significantly lower risk of reporting maternal complications (adjusted relative risk, 0.63; 95% confidence interval, 0.42-0.95), screening positive for depression (adjusted relative risk, 0.55; 95% confidence interval, 0.38-0.81), and reporting newborn complications (adjusted relative risk, 0.74; 95% confidence interval, 0.56-0.97), respectively, than women with low total person-centered maternity care scores. Women with high scores on the supportive care subscale had significantly lower risk of reporting maternal and newborn complications than women with low scores on these subscales (adjusted relative risk, 0.52 [95% confidence interval, 0.42-0.65] and 0.74 [95% confidence interval, 0.60-0.91], respectively). Significant associations were found between all 3 subscale scores and screening positive for depression. Women with high total person-centered maternity care scores were also more likely to adopt a family planning method than those with low scores (adjusted relative risk, 1.25; 95% confidence interval, 1.02-1.52). In particular, women with high scores on the communication and autonomy subscale had significantly higher odds of adopting a family planning method than women with low scores (risk ratio, 1.15; 95% confidence interval, 1.08-1.23). CONCLUSION: Improving person-centered maternity care may improve maternal and newborn health outcomes. Specifically, improving supportive care may decrease the risk of maternal and newborn complications, whereas improving communication and autonomy may increase postpartum family planning uptake.